Performance of Hyperthermia Applicator under ISM Frequency for Breast Cancer Treatment - Naimullah, Bibi Sarpinah Sheikh; Lias, Kasumawati; Jobli, Ahmad Tirmizi; Hassan, Mazlina Mansor; Bakri, Fatimatul Anis; Muhd Yusoff, Muhd Firdaus (Journal of Advanced Research Design, 2025)
Hyperthermia is a treatment procedure that applies heat on the target tissue with a temperature range of 40º to 45º C for a specific duration without affecting the healthy surrounding tissue. The efficacy of hyperthermia treatment relies on the suitable frequency within the Industrial, Scientific, and Medical (ISM) band. The frequency influences both penetration depth and Specific Absorption Rate. This study aims to investigate and compare the performance of the applicator with operating frequencies 434MHz, 915MHz, and 2450MHz with a tumor situated in the middle of the breast phantom. The hyperthermia model is simulated with SEMCAD X. Tissue properties include relative permittivity and conductivity represented with the Generic Dispersive Model. The penetration SAR distribution varies with different frequencies applied to the applicator. The applicator with 434MHz has greater penetration than 915MHz and 2450MHz. The SAR distribution on 2450MHz is more focused on the areola of the breast phantom, while on 915MHz, heat focuses on the middle of the breast phantom. For applicator 434MHz, the heat covers the middle part of the breast phantom to the chest wall. The appropriate applicator is recommended for effective hyperthermia treatment.